For a Semantic-Pragmatic Approach to the Frozen Expressions of Car Brokers in Algeria - Bendib, Hanan (Milev Journal of Research and Studies, 2023)
Algeria’s sociolinguistic situation continues to offer a fertile corpus to the field of language sciences, particularly that of discourse analysis. This study is also responsible for analysing the language practices of Algerian speakers in the world of car sales. Its objective is to clarify and interpret semantically and pragmatically the frozen polylexical sequences of sellers of vehicles in Algerian context. The semantic approach reveals that these sequences have a compositional meaning and are characterized by a criterion of transparency, partial or total opacity depending on the context of use. They also convey specific pragmatic features that reflect the cultural dimension shared by these speakers.